2022
DOI: 10.3390/ijms232012445
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of IBD—Is It Still a Mystery?

Abstract: Inflammatory bowel diseases (IBD), including colitis ulcerosa and Crohn’s disease, are chronic diseases of the gastrointestinal tract for which the cause has not been fully understood. However, it is known that the etiology is multifactorial. The multidirectional network of interactions of environmental, microbiological and genetic factors in predisposed persons lead to an excessive and insufficiently inhibited reaction of the immune system, leading to the development of chronic inflammation of the gastrointes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 62 publications
0
35
0
Order By: Relevance
“…IBDs are chronic disorders characterized by intestinal inflammation and dysregulated gut immune response with loss of intestinal barrier function. 167,168 studies have found that in IBDs microbially derived metabolites impact multiple processes in patients including immune function and mucosal barrier integrity, 169 and that IBD pathogenesis is often driven by alteration of the gut microbiota. 170 Micrbiota-derived metabolites (Figure 5a) that have been implicated in IBDs in both mouse models 171 and patients 172 include short chain fatty acids, phospholipids and sphingolipids, bile acids, indole derivatives, and branched chain amino acids (valine, leucine, isoleucine), among others.…”
Section: Metabolism In Other Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…IBDs are chronic disorders characterized by intestinal inflammation and dysregulated gut immune response with loss of intestinal barrier function. 167,168 studies have found that in IBDs microbially derived metabolites impact multiple processes in patients including immune function and mucosal barrier integrity, 169 and that IBD pathogenesis is often driven by alteration of the gut microbiota. 170 Micrbiota-derived metabolites (Figure 5a) that have been implicated in IBDs in both mouse models 171 and patients 172 include short chain fatty acids, phospholipids and sphingolipids, bile acids, indole derivatives, and branched chain amino acids (valine, leucine, isoleucine), among others.…”
Section: Metabolism In Other Diseasesmentioning
confidence: 99%
“…The utility of RS in early diagnosis of GI diseases has risen in the past decade specifically for inflammatory bowel diseases (IBDs) that include Crohn’s disease (CD) and ulcerative colitis (UC). IBDs are chronic disorders characterized by intestinal inflammation and dysregulated gut immune response with loss of intestinal barrier function. , IBDs currently have no cure, and there are limited treatment options for patients. Recent studies have found that in IBDs microbially derived metabolites impact multiple processes in patients including immune function and mucosal barrier integrity, and that IBD pathogenesis is often driven by alteration of the gut microbiota .…”
Section: Label-free Raman Spectroscopy For Metabolic Profilingmentioning
confidence: 99%
“…Drivers of IBD include a complex interplay of environmental, dietary, genetic, and microbial determinants, that will initiate and perpetuate inflammation of the gastrointestinal tract [ 7 ]. It can occur at any age, from early childhood to adulthood, and can have life-long complications.…”
Section: Introductionmentioning
confidence: 99%
“…1 Currently, the global prevalence of IBD is 90 cases per 100,000 people; this has increased by 31% from 1990 to 2017. 2,3 In South Korea, the prevalence of IBD also increased from 2010 to 2019, more than doubling in the span of 10 years, ranging from 15.1 to 36.9 per 100,000 for CD and 31.4 to 65.7 per 100,000 for UC. 4 Over the past decades, various therapeutics, including biologics and small molecules, have been developed, bringing significant clinical improvements and benefits compared to existing treatments.…”
Section: Introductionmentioning
confidence: 99%